2012
DOI: 10.1039/c2gc16147h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon oxidation generated in diesel engines using iron-doped fuel

Abstract: The soot oxidation activity of metallic iron nanoparticles was studied under real diesel engine conditions. Particulate matter (PM) was sampled at distinct temperatures, using fuels containing ferrocene. The results indicated an 80% reduction of accumulated PM using fuels doped with 50 ppm ferrocene at a temperature of 460• C. Temperature-programmed catalytic oxidation tests indicated that PM oxidation in ferrocene-doped fuels starts at an approximately 200• C lower temperature. The transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The process of Fe nanoparticle formation and oxidation is expected to take place in the cylinder, where high temperatures prevail. Because neither Fe-borne additives (e.g., ferrocene , ) nor biofuels were used during the experiment, the nanosized Fe-oxide particles may have formed via combustion of extremely small quantities of wear materials split off by mechanical abrasion, most likely from the injection system or from other Fe-bearing components of the engine prior to the cylinder. The composition of the particles (Fe with some Mn and Cr), which corresponds to that of an alloy commonly used in engine components, is in line with this assumption.…”
Section: Results Of Tem Imagingmentioning
confidence: 99%
“…The process of Fe nanoparticle formation and oxidation is expected to take place in the cylinder, where high temperatures prevail. Because neither Fe-borne additives (e.g., ferrocene , ) nor biofuels were used during the experiment, the nanosized Fe-oxide particles may have formed via combustion of extremely small quantities of wear materials split off by mechanical abrasion, most likely from the injection system or from other Fe-bearing components of the engine prior to the cylinder. The composition of the particles (Fe with some Mn and Cr), which corresponds to that of an alloy commonly used in engine components, is in line with this assumption.…”
Section: Results Of Tem Imagingmentioning
confidence: 99%
“…Schulz et al reported the soot oxidation activity of metallic iron nanoparticles under real diesel engine conditions [34]. Particulate matter was sampled at distinct temperatures, using fuels containing ferrocene.…”
Section: Catalysismentioning
confidence: 99%
“…24 Aer the addition of ferrocene, primary particle sizes of soot are almost invariant, the agglomerates become smaller, and the crystallite size of soot decreases. 25,26 The effects of ferrocene on ame temperature have been studied in our previous work. 21 However, the study of the inuence of ferrocene on soot nanostructure and functional groups, and their relationships with ame temperature and soot oxidation is limited.…”
Section: Introductionmentioning
confidence: 99%